Altered Balance between Vasoconstrictor and Vasodilator Systems in Experimental Hypertension - Zicha, J; Vaněčková, I (Physiological research, 2024)
Sympathetic hyperactivity and relative NO deficiency are characteristic alterations in both genetic and salt hypertension. The contribution of these abnormalities to blood pressure (BP) maintenance can be determined in conscious rats using a consecutive blockade of particular vasoactive systems. Thus, the contribution of pressor effects of angiotensin II to the maintenance of high BP is usually small, but the role of renin-angiotensin system in the development of hypertension mediated by central and peripheral effects of angiotensin II on sympathetic activity is highly important. This is even true in angiotensin-dependent hypertension of heterozygous Ren-2 transgenic rats in which sympathetic hyperactivity is increasing with age. Central sympathoexcitation in this hypertensive model can be inhibited by lower losartan doses than peripheral angiotensin II-dependent vasoconstriction. This experimental model also yielded important knowledge on nephroprotective effects of new therapeutic drugs - endothelin receptor type A blockers. A considerable part of sympathetic vasoconstriction is dependent on the interaction of Ca2+ sensitization (RhoA/Rho kinase pathway) and Ca2+ influx (through L-VDCC). The blockade of these pathways prevents a major part of sympathetic vasoconstriction. Ca2+ sensitization seems to be attenuated in genetic hypertension in order to compensate increased Ca2+ influx. In contrast, enhanced Ca2+ sensitization is a hallmark of salt sensitivity in Dahl rats in which salt hypertension is dependent on increased Ca2+ influx. The attention should also be paid to the impairment of arterial baroreflex sensitivity which permits enhanced BP responses to pressor or depressor stimuli. Some abnormalities can be studied in blood vessels isolated from hypertensive rats but neither conduit arteries nor mesenteric resistance arteries represent the vascular beds decisive for the increased peripheral resistance and high BP. Keywords: Sympathetic vasoconstriction, NO-dependent vasodilatation, Calcium sensitization, Calcium influx, Arterial baroreflex, Spontaneously hypertensive rats, Salt hypertensive Dahl rats, Ren-2 transgenic rats, RAS blockade, SNS blockade, NOS inhibition, Endothelin, Vascular contraction and relaxation, Isolated conduit and resistance arteries, EDCF, PGI2, BKCa channels.
Keywords: Blood Pressure; Disease Models, Animal; Vasoconstriction; Vasodilation; modely nemocí na zvířatech; vazokonstrikce; Renin-Angiotensin System; vazodilatace; hypertenze; sympatický nervový systém; Animals; lidé; krevní tlak; Sympathetic Nervous System; renin-angiotensin systém; Hypertension; zvířata; Humans